Study on ova structure of different gonadal stages of some Small Indigenous Fishes - Pachiang, Gracy; Minare, Anubhuti; Vyas, Vipin (AG Volumes, 2025)
The present study was conducted to examine the ova structure and fecundity patterns across different gonadal maturity stages in selected Small Indigenous Fish Species (SIFS). The investigation was carried out over a five-month period from August to December 2023 at the Laboratory of the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal. Specimens were collected from multiple fish markets across Bhopal, including Kasturba, Vijay, Piplani, and Govindpura markets. Six species were selected for the study: Rasbora daniconius, Amblypharyngodon mola, Gudusia chapra, Puntius ticto, Heteropneustes fossilis, and Clarias batrachus. Total length, weight, fecundity, and ova diameter were recorded monthly. Ova diameter was measured using an ocular micrometer under a compound microscope, while fecundity was estimated using gravimetric methods by analyzing subsamples from different ovarian regions. Histological slides were prepared through alcohol dehydration, xylene clearing, eosin staining, and DPX mounting for structural observation of ova at various maturity stages. The study revealed significant interspecies and seasonal variations in fecundity and ova diameter. For instance, the maximum and minimum Fecundity for Rasbora daniconius are 13,912.29 in August and 3081 in September. For Gudusia chapra, the maximum and minimum Fecundity are 10,900 in September and 7013.83 in August. For Puntius ticto, the maximum and minimum Fecundity were found to be 23510.09 in August and 931 in November. For Amblypharyngodon mola, the maximum and minimum Fecundity were found to be 12147.07 in August and 1415.80 in September. For Heteropneustes fossilis, the maximum and minimum Fecundity were found to be 19208.48 in September and 15174.77 in August, and for Clarias batrachus, the maximum and minimum Fecundity were found to be 18320 in August and 10564.2 in September. These findings contribute to a better understanding of reproductive biology in indigenous fish species, which is essential for their conservation, captive breeding programs, and sustainable aquaculture development.